Implementation of a Business Model in a Broiler Chicken Partnership Company: A Case Study of PT Mustika Jaya Lestari - Hanggiani, Anggi; Lashyadi, Alva; Perdhana, Mirwan Surya; Kusumawardhani, Amie (Research Horizon, 2024)
The form of partnership between breeders and core companies is a mutually beneficial relationship, however, this is a collaboration that needs to be accompanied by monitoring and guidance. This collaboration of course requires a business model that is accepted by both parties. This research aims to create a sustainable and mutually beneficial broiler chicken partnership company strategy through the Business Model Canvas approach. This research uses qualitative analysis. The sample in this study were the head of head office divisions and the branch heads of partnership companies. Meanwhile, the partner sample is from some partners who use closed houses and open houses. This study uses business model canvas analysis and SWOT analysis. The results of the study show that the strategies formed from the SWOT matrix are increasing the number of branches in Indonesia, developing integrated applications for farmers, strengthening brands for personal, business and services, establishing Chicken Slaughterhouses, partnering with sapronak companies, loyalty programs for employees, cascading monitoring with new technology, online recruitment and the use of professional management.